2021
DOI: 10.1016/j.cities.2021.103196
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on barriers and opportunities for integrating urban agri-green roofs: A European Mediterranean compact city case

Abstract: The main objective of this study is to analyse the barriers and opportunities with regard to the implementation of urban agri-green roofs (UAGR) in cities. The case study was conducted in Barcelona, a Mediterranean compact city. The World Café methodology and a semi-quantitative analysis were used in this work. Five categories of barriers and opportunities were discussed (social, environmental, legal/administrative, technological/architectural, and economic) by interdisciplinary stakeholders.In total, 103 barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…However, research on this issue is still recent, and further empirical evidence is necessary to validate the findings in different contexts. This study further revealed that stakeholders perceived the cost of water as a "hindering" factor, which had not been identified previously (Cerón-Palma et al, 2012;Specht et al, 2015Specht et al, , 2016aSanyé-Mengual et al, 2016;Specht and Sanyé-Mengual, 2017;Zambrano-Prado et al, 2021). Water for irrigation of crops can be expensive in urban areas.…”
Section: Context Factors and Their Perceived Degree Of Hindering Or Promoting Ruamentioning
confidence: 64%
See 2 more Smart Citations
“…However, research on this issue is still recent, and further empirical evidence is necessary to validate the findings in different contexts. This study further revealed that stakeholders perceived the cost of water as a "hindering" factor, which had not been identified previously (Cerón-Palma et al, 2012;Specht et al, 2015Specht et al, , 2016aSanyé-Mengual et al, 2016;Specht and Sanyé-Mengual, 2017;Zambrano-Prado et al, 2021). Water for irrigation of crops can be expensive in urban areas.…”
Section: Context Factors and Their Perceived Degree Of Hindering Or Promoting Ruamentioning
confidence: 64%
“…In addition, financial incentives, the development of new technologies, education, food production and local policies such as the Milan urban food policy pact and Parisculteurs program were identified in this study as "promoting" RUA. Policies targeting the development of new technology not found in the previous literature (Cerón-Palma et al, 2012;Specht et al, 2015Specht et al, , 2016aSanyé-Mengual et al, 2016;Specht and Sanyé-Mengual, 2017;Zambrano-Prado et al, 2021) were also identified by the stakeholders in this study, possibly due to the involvement of academics. This finding is relevant for exploring techniques, procedures, and resource efficiencies for RUA.…”
Section: Policies and Their Perceived Effects On Hindering Or Promoting Ruamentioning
confidence: 72%
See 1 more Smart Citation
“…These can vary from legislation deficiency to clime characteristics or cost. On the other hand, positive aspects such as life quality enhancement, good opportunities for landscape painters to expand, or aesthetic enhancement need to be mentioned [11].…”
Section: City Life Improvementmentioning
confidence: 99%
“…Faced with this reality, cities such as Barcelona have begun to tackle the climate challenge vigorously in areas such as urban mobility and energy efficiency while also integrating elements of social welfare. But these actions are still perceived as distant by citizens who report barriers such as lack of information, scepticism, feelings that some measures will bring more problems than benefits, or lack of social cohesion, including low community involvement (Echavarren et al ., 2019; Geiger and Swim, 2016; Zambrano-Prado et al ., 2021). Regardless of the barriers perceived by citizens, the global agreement is that all cities will experience the effects of climate change to a greater or lesser extent through different impacts on their urban metabolism and infrastructure and will suffer increased risk and vulnerability.…”
Section: Introductionmentioning
confidence: 99%